'Sowing the seeds of community': Daycare managers participating in a community approach project. (November 2020) - Achituv, Sigal; Hertzog, Esther
This paper is based on a study of daycare center managers participating in a project aimed at changing the communal approach in early childhood education (ECE) centers. The project was implemented by the ECE system of Israel's Association of Community Centers for ages birth to three, based on the Ecological Systems Theory (Bronfenbrenner, 1979). The study aimed at learning about the managers' views and attitudes toward the project, expanding knowledge in the sphere of ECE management and proposing relevant methods for policy improvement. The study applied qualitative methodology and was based on in-depth interviews with managers who participated in the first year of the project, and on observations at the daycare centers and on the project's implementation process. The findings reveal that the managers are influenced in various ways, by the complex economic and organizational reality of their workplace. The position of the daycare managers as responsible for both implementing the project's policies and for managing the caregivers creates a complex identity informed by ambivalent attitudes toward the system and the project itself. As ECE for ages birth to three is a conspicuous subject on international public agendas, this study may help ECE policymakers improve education systems by developing solid communal policies.